EDUCATIONAL PHILOSOPHY OF MAHATMA GANDHI AND ITS RELEVANCE IN PRESENT EDUCATIONAL SCENARIO (International Journal of Food and Nutritional Sciences, 2022)
Mahatma Gandhi an idealist, pragmatist and naturalist philopsher and his educational philosophy is based on his philosophy of his life.Gandhiji made a special contribution to education. He was the first Indian to support an educational programme built around the core principles of Indian cultures and civilization.(Selvan and Devanesan, 2020) In this paper an attempt has been made to discuss the educational philosophy of Mahatma Gandhi and its relevance to the present scenario. Descriptive method and secondary sources of data has been used for the present study.